A Study on the Genetic Inheritance of Ankyloglossia Based on Pedigree Analysis - Soo-Hyung Han; Min-Cheol Kim; Yun-Seok Choi; Jin-Soo Lim; Ki-Taik Han (Archives of Plastic Surgery, 2012)
Background Ankyloglossia or tongue-tie is a congenital anomaly characterized by an abnormally short lingual frenum. Its prevalence in the newborn population is approximately 4%. Its mode of inheritance has been studied in some articles, but no conclusion has been established. Also, no relevant report has been published in Korea. This study was conducted to elucidate the genetic inheritance of ankyloglossia via pedigree analysis. Methods In this study, 149 patients with no other congenital anomaly who underwent frenuloplasty between March 2001 and March 2010 were studied. Pedigrees were made via pre- or post-operative history taking, and patients with uncertain histories were excluded. In the patient group that showed a hereditary nature, the male-to-female ratio, inheritance rate, and pattern of inheritance were investigated. Results One hundred (67.11%) of the patients were male and 49 (32.89%) were female (male-female ratio=2.04:1). Ninety-one (61.07%) patients reported no other relative with ankyloglossia, and 58 (38.93%) patients had a relative with this disease. The inheritance rate was 20.69% in the 58 cases with a hereditary nature. In the group with no family history of ankyloglossia, the male-female ratio was 3.79:1, which significantly differed from that of the group with a family history of ankyloglossia. X-chromosome mediated inheritance and variation in the gene expression was revealed in the pedigree drawn for the groups with hereditary ankyloglossia. Conclusions Ankyloglossia has a significant hereditary nature. Our data suggest X-linked inheritance. This study with 149 patients, the first in Korea, showed X-linked inheritance in patients with a sole anomaly.